Comparative analysis of the modulation of perineuronal nets in the prefrontal cortex of rats during protracted withdrawal from cocaine, heroin and sucrose self-administration. (1st December 2020) - Roura-Martínez, David; Díaz-Bejarano, Paula; Ucha, Marcos; Paiva, Raquel R.; Ambrosio, Emilio; Higuera-Matas, Alejandro
Abstract: Relapse into drug use is a significant problem for people recovering from addiction. The ability that conditioned cues have to reinstate and reinvigorate drug-seeking is potentiated over time (incubation of seeking), posing an additional difficulty for maintaining abstinence. While the prefrontal cortex has been involved in the incubation phenomenon and the extracellular matrix, perineuronal nets (PNNs) in particular, may play a vital role in brain plasticity associated to drug relapse, there are no comparative analyses between different drug classes and natural reinforcers. Here, we compare the effects of early (1 day) and protracted (30 days) withdrawal from to cocaine, heroin and sucrose self-administration on the total density and density per intensity range of PNNs of different territories of the prefrontal cortex of male Lewis rats. Our results show that cocaine self-administration increases the density of PNNs in the dorsal prelimbic, infralimbic and ventral orbitofrontal cortices, while protracted withdrawal reversesthis effect in the dorsal prelimbic cortex. Also, heroin self-administration increases the density of PNNs in the infralimbic cortex and ventral orbitofrontal cortices, but this effect is lost after 30 days of withdrawal in the infralimbic cortex. Finally, the self-administration of sucrose-sweetened water or the protracted withdrawal from this powerful reinforcer does not affect any of the PNN parameters analysed. Our results show that two different drugs of abuse (but not a natural reward) with specific pharmacological and physiological actions, differentially modulate PNNs in specific areas of the rodent prefrontal cortex with potential implications for the incubation of seeking phenomenon. Highlights: PNN density increases in the dPL, vPL, IL and vOFC after cocaine self-administration. Thirty days of withdrawal reversed cocaine effects in the dPL. PNN density increases in the right IL and vOFC after heroin SA. Protracted withdrawal reversed this effect in the IL. Hemisphere-specific effects.